2021
DOI: 10.1111/ene.15066
|View full text |Cite
|
Sign up to set email alerts
|

Higher‐quality diet and non‐consumption of meat are associated with less self‐determined disability progression in people with multiple sclerosis: A longitudinal cohort study

Abstract: Background and purpose: Modifiable lifestyle factors, including diet, may affect clinical outcomes in multiple sclerosis (MS). This study assessed the relationships between diet, and disability, fatigue, and depression risk in people with MS.Methods: Participants from the Health Outcomes and Lifestyle In a Sample of people with Multiple sclerosis (HOLISM) international cohort were assessed over 2.5 years.Dietary data were obtained using a modified Diet Habits Questionnaire (DHQ), disability using the calculate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
17
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 51 publications
6
17
1
Order By: Relevance
“…24 A second recent meta-analysis of randomized, controlled trials found that probiotic supplementation improved mental health among people with MS. 25 Furthermore, omega-3 fatty acid supplementation was found to have no effect on disability status but did significantly reduce serum tumor necrosis factor-α, a marker of inflammation. 26 In addition, several observational studies have shown that higher diet quality is associated with reduced risk of MS [27][28][29] and reduced relapse rate, disability status, brain volume loss, fatigue, cognitive impairment, depression, and increased physical and mental QoL among people with MS. [30][31][32][33][34][35] Based on the associations of weight with comorbidity burden, weight loss with reduced MS disability, and the microbiome and metabolites with the immune system, the National MS Society recommends "general healthy" diet changes. 36 The current state of evidence as of 2019 did not support recommendations for any specific dietary approach, 8 thus necessitating the Nation MS Society's recommendation for a general healthy diet.…”
Section: Physical Qolmentioning
confidence: 99%
“…24 A second recent meta-analysis of randomized, controlled trials found that probiotic supplementation improved mental health among people with MS. 25 Furthermore, omega-3 fatty acid supplementation was found to have no effect on disability status but did significantly reduce serum tumor necrosis factor-α, a marker of inflammation. 26 In addition, several observational studies have shown that higher diet quality is associated with reduced risk of MS [27][28][29] and reduced relapse rate, disability status, brain volume loss, fatigue, cognitive impairment, depression, and increased physical and mental QoL among people with MS. [30][31][32][33][34][35] Based on the associations of weight with comorbidity burden, weight loss with reduced MS disability, and the microbiome and metabolites with the immune system, the National MS Society recommends "general healthy" diet changes. 36 The current state of evidence as of 2019 did not support recommendations for any specific dietary approach, 8 thus necessitating the Nation MS Society's recommendation for a general healthy diet.…”
Section: Physical Qolmentioning
confidence: 99%
“…Our internal consistency results demonstrated a weak effect of the sub-scores and our findings also show that the DHQ sub-scores are targeted in assessing the overall diet quality for people with RRMS. While studies have used the total DHQ data as indicative of higher versus lower quality of intake, generally [ 32 ], they are unable to differentiate between the complex interrelationships that patterns of eating reflect. Despite this, a recent analysis did find an influence of meat intake as was also found in our analysis [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…While studies have used the total DHQ data as indicative of higher versus lower quality of intake, generally [ 32 ], they are unable to differentiate between the complex interrelationships that patterns of eating reflect. Despite this, a recent analysis did find an influence of meat intake as was also found in our analysis [ 32 ]. The study also used the HOLISM data providing support for the findings from our smaller sample.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the effect of dietary interventions on MS outcomes has been studied, with the overwhelming majority of studies examining food supplements rather than overall diet quality. An observational study identified an association between a healthier diet and higher mental and physical health quality of life scores; a dose-response relationship was observed between diet habits questionnaire score and quality of life score 74 . In a second study, healthier dietary intake on subscales for fibre, fruit and vegetables, and fat was associated with better quality of life scores 75 .…”
Section: Intermediate Determinantsmentioning
confidence: 99%